2019
DOI: 10.1002/jnr.24389
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction and neonatal hypoxic ischemic brain injury causes sex‐specific long‐term neurobehavioral abnormalities in rats

Abstract: There is a lack of knowledge of factors preventing an adequate response to moderate hypothermia after hypoxic ischemic (HI) brain injury. We hypothesized that growth restriction from reduced intrauterine perfusion would predispose neonatal rats to have a worse outcome with HI brain injury. IUGR was induced by placental insufficiency in dams at 14 days of gestation. HI was induced at postnatal day (P) 10 by permanent right carotid artery ligation followed by 90 min of hypoxia (8% oxygen). Tests for early brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Downregulation of placental IGF1R might be an important factor in pregnancies complicated by intrauterine growth restriction (IUGR) 29 . Recent report has also shown a significant downregulation of IGF1R protein levels in IUGR pregnancies compared to normal pregnancies 30,31 . Interestingly, IGF1R protein downregulation in IUGR placentas was accompanied by impaired activation of intracellular signaling molecules of the IGF1R 32,33 .…”
Section: Introductionmentioning
confidence: 85%
“…Downregulation of placental IGF1R might be an important factor in pregnancies complicated by intrauterine growth restriction (IUGR) 29 . Recent report has also shown a significant downregulation of IGF1R protein levels in IUGR pregnancies compared to normal pregnancies 30,31 . Interestingly, IGF1R protein downregulation in IUGR placentas was accompanied by impaired activation of intracellular signaling molecules of the IGF1R 32,33 .…”
Section: Introductionmentioning
confidence: 85%
“…A number of clinical studies have identified male sex as an independent risk factor for poor neurodevelopmental outcomes in prematurity (Hintz et al, 2006;Sunny et al, 2020) and hypoxic-ischemic (HI) injury (Mirza et al, 2015;Narang et al, 2019). A sex bias has also been identified in children with CP, with males being more affected than females (Johnston and Hagberg, 2007).…”
Section: Discussionmentioning
confidence: 99%